Upacara Ngaturang Cicipan di Pura Jamintura Desa Banyu Urip (Perspektif Pendidikan Agama Hindu) - I Made Ardika Yasa (Jayapangus Press, 2020)
This paper contains the implementation of Hindu Religious Education in the implementation of the Ngaturang Cicipan Ceremony in Rincung, Banyu Urip Village, Gerung Subdistrict, West Lombok Regency. This ceremony was formerly initiated by the Subak Association and Rincung residents who work as farmers, but now it has been participated by all Rincung residents and Balinese Hindu’s people. Hindu Balinese who live in Banyu Urip Village was held a ceremony once a year at Purnama Sasih Kasa, when all residents who are farmers have finished carrying out the harvest as a form of thanks to God, the abundant harvest and the blessing of the God Indra to be blessed with Rain so that the fertility of their paddy fields is maintained. The approach in this paper is descriptive qualitative. The data was collected through observation and interviews. The collected data is compile based on the original reality forming a description in accordance with the object being observed. Based on the data collected, it can be stated that there is an implementation of Hindu religious education values ​​in the implementation of the Ngaturang Cicipan ceremony that has been carried out by the Subak Association in Rincung, Banyu Urip village, Gerung District, West Lombok Regency.